2016
DOI: 10.1177/0956462415618109
|View full text |Cite
|
Sign up to set email alerts
|

Lupus erythematosus-lichen planus overlap syndrome in an HIV-infected individual

Abstract: Lupus erythematosus-lichen planus (LE-LP) overlap syndrome is an uncommon disorder with clinical, histological and/or immunopathological features of both diseases. We report a case of LE-LP overlap syndrome in a patient with HIV infection. To the best of our knowledge, LE-LP overlap syndrome with HIV infection has never been reported in literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“… 9 , 10 , 11 , 12 In total, 38 cases of CLE/LP overlap syndrome were identified. 1 , 2 , 3 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 Of these 38 cases, 12 were classified as “classic,” 21 were classified as “possible,” and 5 had incomplete workup and thus were unable to be classified as CLE/LP overlap syndrome according to our criterion. Demographic information, clinical features, histologic features, immunofluorescence, serologic findings, laboratory findings, treatments, and treatment responses in these cases are summarized in Table II .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 9 , 10 , 11 , 12 In total, 38 cases of CLE/LP overlap syndrome were identified. 1 , 2 , 3 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 Of these 38 cases, 12 were classified as “classic,” 21 were classified as “possible,” and 5 had incomplete workup and thus were unable to be classified as CLE/LP overlap syndrome according to our criterion. Demographic information, clinical features, histologic features, immunofluorescence, serologic findings, laboratory findings, treatments, and treatment responses in these cases are summarized in Table II .…”
Section: Discussionmentioning
confidence: 98%
“… Not reported. Classic overlap Patil et al 14 40 yo; F Multiple erythematous to depigmented atrophic scaly plaques with peripheral hyperpigmentation on extensors of both upper and lower extremities and back. Buccal erosions with scalloped borders and diffuse cheilitis.…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal involvement was predominantly seen in our patients compared to cases reported in literature. [ 3 4 5 8 9 10 11 12 13 ] Buccal mucosa was the most commonly affected mucosa, and reticulate type of LP was the most common.…”
Section: Discussionmentioning
confidence: 99%
“…To date, ~50 cases of LP/LE overlap syndrome have been reported, most of whom are between 25 and 45 years old, with a predominance of women ( 4 ). There is controversy about LP/LE overlap syndrome should be an independent diagnosis specifically for the coexistence of LE and LP as it has been reported that patients have separate lesions consistent with each disease.…”
Section: Discussionmentioning
confidence: 99%